2021
DOI: 10.1016/j.celrep.2021.109580
|View full text |Cite
|
Sign up to set email alerts
|

Fusion pores with low conductance are cation selective

Abstract: Highlights d Exocytotic transmitter release is an electrodiffusion process d Narrow fusion pores are cation selective d Fusion pore ion selectivity decreases as the fusion pore expands

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Alternatively, it has been reported that the fusion pore is cation-selective ( 31 ). Since both Alexa 488 and CF488A are anionic, it is possible that the delay in external dye entry may be due to electrostatic repulsion.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, it has been reported that the fusion pore is cation-selective ( 31 ). Since both Alexa 488 and CF488A are anionic, it is possible that the delay in external dye entry may be due to electrostatic repulsion.…”
Section: Resultsmentioning
confidence: 99%
“…However, surprisingly, in many other cases, apparent fluctuations of a foot signal preceding a spike were the result of overlapping catecholamine release activity at different locations, suggesting that distant exocytotic events and foot signals may occur in a synchronized manner. Thus, the interpretation of amperometric foot signals may seem less straightforward than typically assumed [ 43 ].…”
Section: Frontier Advances Reported At the Isccb-21 Meeting In Hamburgmentioning
confidence: 99%
“…Alternatively, it has been reported that the fusion pore is cation-selective (Delacruz et al, 2021). Since both Alexa 488 and CF488A are anionic, it is possible that the delay in external dye entry may be due to electrostatic repulsion.…”
Section: The Fusion Pore Can Limit Entry Of External Dyementioning
confidence: 99%